Dampak Kinerja Keuangan Lembaga Zakat Terhadap Tingkat Kemiskinan Melalui Penyaluran Zakat - Fitri Auliani; Iwan Setiawan; Kristianingsih Kristianingsih (Journal of Applied Islamic Economics and Finance, 2022)
This study was conducted to analyze the financial performance of zakat institutions. Then how does the financial performance affect the level of zakat distribution and its impact on the poverty level in Indonesia in 2012 - 2019. The results of this study indicate that the financial performance of zakat institutions is still not effective and efficient enough. The activity ratio and the liquidity ratio have a significant negative effect on the distribution of zakat. The efficiency ratio, the ratio of amil funds and the growth ratio have no significant effect on the distribution of zakat. The activity ratio and the liquidity ratio have a significant negative effect on the poverty level through the distribution of zakat. The efficiency ratio, the ratio of amil funds and the growth ratio have no significant effect on the level of the poor through the distribution of zakat.